Exploring the Impact of Social Media Marekting on Consumer Purchasing Decisions: Study on Northern Part of Bangladesh - Kabir, Md Rishad; Laila Khatun (Universitas Airlangga, 2026)
Purpose: The study aims to investigate the influence of social media marketing on customer purchase decision in semi urban region of northern part of Bangladesh like Rangpur. It focuses on identifying the critical factors such as influencer marketing, social media engagement, user generated content, Frequency of post and social media advertising strategy that significantly affect consumer behavior in this socio economic context. Methodology: Quantitative data was gathered from 212 social media users in Rangpur using convenience sampling. The data was examined using descriptive and inferential statistical techniques. Findings: Principal findings indicate that user-generated content and influencer marketing are the most significant determinants influencing customer purchasing decisions. Moreover, social media involvement, advertising approach, and post frequency favorably influence customer behavior. Practical Implication: The study emphasizes the significance of utilizing user-generated content, partnering with local influencers, and developing data-driven, tailored campaigns to improve trust, engagement, and sales. It underscored the necessity for culturally customized and economically viable techniques to tackle the socio-economic circumstances of Rangpur's semi-urban consumers, providing significant insights for marketers in analogous emerging areas. Originality: This research enhances previous literature by providing a localized perspective on the effects of social media marketing in a semi-urban region of Bangladesh. It emphasizes the significance of new marketing methods, like influencer marketing and user-generated content, while offering actionable insights for firms seeking to effectively interact with consumers in developing nations. Limitations: The dependence on non-probability sampling impairs generalizability and concentrates on a specific demography in Rangpur, hence restricting wider application. Moreover, the brief data collecting interval may fail to reflect the enduring changes in customer behavior. Subsequent study ought to examine these concerns and investigate other contributing variables.